Design, Modeling, and Vibration Control of a Damper Based on Magnetorheological Fluid and Elastomer - Zhuang Jin; Fufeng Yang; Xiaoting Rui; Min Jiang; Jiaqi Wang (Actuators, 2024)
The aim of this study is to propose a damper based on magnetorheological (MR) fluid and elastomer for application in vehicle engine mounting systems to dissipate the vibration energy transferred from the engine to the vehicle body. The magnetic circuit structure of the damper has been precisely designed, and its reasonableness has been verified by static magnetic field simulation. After the principle prototype’s completion, the damper’s mechanical properties are tested by an electro–hydraulic servo fatigue machine. The results show that with the current increase, the damper’s in-phase stiffness increases by 20.6%. The equivalent damping improves by 81.6%, which indicates that the damper has a good MR effect. A new phenomenological model is proposed, and a genetic algorithm is used to identify the parameters of the model. Finally, a 1/4 vehicle engine vibration damping system model is established and a dynamics simulation is carried out. The simulation results show that the damper effectively reduces the vibration transmitted from the engine to the body, and the vibration-damping effect is even more obvious through sky-hook control. This proves that the damper proposed in this study has good vibration-damping performance.